(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2025)
The current study sought to determine the role of organizational fortification through its indicators (strengthening the self-structure of employees, rationalizing cultural discourse, erasing negative control, accepting and recognizing others) in containing technical risks. The problem of the study was defined in the following question: Do the negative effects constitute technical risks and determinants of the organization under study? In order to adopt the process of organizational fortification, it also adopted a hypothesis that the dimensions expressing the containment of technical risks (the economic dimension, the social dimension, the technical dimension) are affected by the level of organizational fortification prevailing in the organization under investigation. The survey list was adopted as a main tool for collecting data if it was distributed to a random sample consisting of (30) individuals in various Organizational levels in Zakho dairy factory. The researchers used a set of statistical tools (frequencies, arithmetic mean, standard deviation, correlation coefficient, regression) to describe and analyze the phenomenon under study, as well as to test the hypothesis of the study. The study concluded with a number of conclusions, the most notable of which is the presence of a positive trend among the respondents regarding indicators of organizational fortification through answers to expressive statements. This facilitates the process of containing technical risks at the level of the researched organization, In addition to the existence of correlations and influence between the two variables of the study (organizational fortification and technical risks), the study presented several recommendations, the most prominent of which is the necessity of adhering to organizational fortification, which is considered one of the basic foundations that the organization under study must adopt because it ensures its inviolability from any technical risks